2017
DOI: 10.1016/j.ypmed.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence outcomes of 771 intervention trials: Systematic review and meta-analysis

Abstract: Excellent medication adherence contributes to decreases in morbidity, mortality, and health care costs. Although researchers have tested many interventions to increase adherence, results are sometimes conflicting and often unclear. This systematic review applied meta-analytic procedures to integrate primary research that tested medication adherence interventions. Comprehensive searching completed in 2015 located 771 published and unpublished intervention studies with adherence behavior outcomes. Random-effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
231
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(272 citation statements)
references
References 29 publications
6
231
0
6
Order By: Relevance
“…The highest adherers commonly reported that they did their treatments automatically, indicating that it was habitual. This is consistent with recent research showing the importance of automatic motivation habits in adherence (Hoo et al ., ; Phillips, Cohen, Burns, Abrams, & Renninger, ), including evidence that adherence interventions that focus on habit formation are the most effective (Conn & Ruppar, ). Habits mean that adherence requires less cognitive effort (Gardner, de Bruijn, & Lally, ), and this means that habits can be maintained in circumstances that might make treatment taking more challenging (Gardner, ).…”
Section: Discussionmentioning
confidence: 99%
“…The highest adherers commonly reported that they did their treatments automatically, indicating that it was habitual. This is consistent with recent research showing the importance of automatic motivation habits in adherence (Hoo et al ., ; Phillips, Cohen, Burns, Abrams, & Renninger, ), including evidence that adherence interventions that focus on habit formation are the most effective (Conn & Ruppar, ). Habits mean that adherence requires less cognitive effort (Gardner, de Bruijn, & Lally, ), and this means that habits can be maintained in circumstances that might make treatment taking more challenging (Gardner, ).…”
Section: Discussionmentioning
confidence: 99%
“…The keywords used in the search strategy were obtained from several previous systematic reviews in the field of medication adherence . The search strategy was based on two queries that were combined together to perform the search.…”
Section: Methodsmentioning
confidence: 99%
“…The keywords used in the search strategy were obtained from several previous systematic reviews in the field of medication adherence. [21][22][23][24] The search strategy was based on two queries that were combined together to perform the search. The first search query was based on the title search using phrases such as 'medication adherence' or 'adherence to medication'.…”
Section: Search Strategymentioning
confidence: 99%
“…This is key for identifying reasons why patients do not adhere to their recommended treatment as addressing perceptual barriers, through behavioural-targeted interventions, have been shown to be more effective for improving adherence than addressing non-perceptual barriers [35]. A recent review of determinants of inhaler adherence in adults based on observational data linked adherence to a strong perceived need for medication (necessity beliefs); no other determinants were found to be predictive [36].…”
Section: Introductionmentioning
confidence: 99%